Enhanced Downstream Processing for a Cell-Based Avian Influenza (H5N1) Vaccine - Fang Li; Bo Liu; Yu Xiong; Zhegang Zhang; Qingmei Zhang; Ran Qiu; Feixia Peng; Xuanxuan Nian; Dongping Wu; Xuedan Li; Jing Liu; Ze Li; et al. (Vaccines, 2024)
H5N1 highly pathogenic avian influenza virus (HPAIV) infections pose a significant threat to human health, with a mortality rate of around 50%. Limited global approval of H5N1 HPAIV vaccines, excluding China, prompted the need to address safety concerns related to MDCK cell tumorigenicity. Our objective was to improve vaccine safety by minimizing residual DNA and host cell protein (HCP). We developed a downstream processing method for the cell-based H5N1 HPAIV vaccine, employing CaptoTM Core 700, a multimodal resin, for polishing. Hydrophobic-interaction chromatography (HIC) with polypropylene glycol as a functional group facilitated the reversible binding of virus particles for capture. Following the two-step chromatographic process, virus recovery reached 68.16%. Additionally, HCP and DNA levels were reduced to 2112.60 ng/mL and 6.4 ng/mL, respectively. Western blot, high–performance liquid chromatography (HPLC), and transmission electron microscopy (TEM) confirmed the presence of the required antigen with a spherical shape and appropriate particle size. Overall, our presented two-step downstream process demonstrates potential as an efficient and cost-effective platform technology for cell-based influenza (H5N1 HPAIV) vaccines.